Formulation and Physical Stability Test Preparation of Anti-Acne Gel Extract of Tebu Leaves (Saccharum officinarum (Linn) as Antibacterial Against Staphylococcus Epidermis - Arif Wijayanto; Juvita Herdianty (Universitas STRADA Indonesia, 2022)
Increased processing of Tebu as sugar causes the resulting waste, namely the shoots of Tebu leaves. The phenolic and flavonoid compounds in Tebu are reported to have strong antioxidant, anti-inflammatory, antimutation and tyrosine inhibitor activities. Infectious diseases are diseases caused by the presence of pathogenic microbes, one of which causes infection, namely bacteria. Utilization of Tebu waste is expected to produce alternative products in the form of antibacterial preparations, especially anti-acne. Staphylococcus epidermis is one of the bacteria that causes infection on skin with acne. This study aims to determine the physical stability of the preparation Tebu leaf extract anti acne gel and its antibacterial activity against Staphylococcus Epidermis bacteria. Methods: This research design is an experimental method, making Tebu leaves extract by weighing as much as 400 grams of fine powder of Tebu leaves then put in a maceration container, closed then added 70% 2 liters of ethanol until completely submerged and stored for 24 hours protected from direct sunlight while stirring occasionally. Then filtered, separated the dregs and filtrate. The dregs were re-extracted with the same amount of new 70% ethanol for 2 days. The obtained 70% ethanol filtrate was evaporated to obtain a thick extract using a Vacuum Rotary Evaporator. Tebu leaves extract gel was made at a concentration of 5%, 10%, 15% and an antibacterial test was carried out using the well diffusion method. Results: The results of the physical stability test of the acne extract cream showed that the results met the requirements both in terms of pH, dispersion test, homogeneity. The results of the antibacterial test of Tebu leaves extract showed the presence of a zone of bacterial inhibition which was indicated by the presence of a clear area around the well. Conclusion: The results of the evaluation showed that the Tebu leaves extract gel met the requirements for the physical quality of the gel preparation, both organoleptic, pH, viscosity, adhesion, and spreadability. Tebu leaves extract gel was able to inhibit the growth of S. epidermis bacteria with the best concentration in 3rd formula, consentration 15% Tebu leaves extract gel.